PERANCANGAN KEMASAN SUSHI KEDAI MIE RAMEN GOR H. AGUS SALIM PADANG - FAJRI ILHAM, Dra. Zubaidah, M.Sn., San Ahdi, M.Sn., M.Ds. (DEKAVE : Jurnal Desain Komunikasi Visual, 2016)
Sushi is one of the traditional food from Japan, made from rice and slices of fish meat. At the present time the meal can be found in the city of Padang, housed in GOR. H Agus Salim with outlets named is "KEDAI MIE RAMEN". Design Packaging Sushi Food "KEDAI MIE RAMEN" adapting elements from Japan with to confirm that the product is original food from Japan.Data analyst method used is SWOT for the author to redesign existing packaging designs to be consider, strengths, weaknesses, opportunities and threats that can increase the excellence of the product from competitors' products.The product requires a package which aims to wrap the food in order to avoid direct contact by the outside air, on the other hand the packaging also has a function as the identity of a product issued by businesses, through attractive packaging can be used as a media campaign to introduce a product to prospective customers.Keywords: Packaging Design, Product, Kedai Mie Ramen